Intravenous immunoglobulins improve the function and ameliorate joint involvement in systemic sclerosis: a pilot study. Issue 7 (7th March 2007) - Nacci, F; Righi, A; Conforti, M L; Miniati, I; Fiori, G; Martinovic, D; Melchiorre, D; Sapir, T; Blank, M; Shoenfeld, Y; Pignone, A Moggi; Cerinic, M Matucci
Abstract : Background: In systemic sclerosis (SSc), joint involvement may reduce the functional capacity of the hands. Intravenous immunoglobulins have previously been shown to benefit patients with SSc. Aim: To verify the efficacy of intravenous immunoglobulins on joint involvement and function in SSc. Patients and methods: 7 women with SSc, 5 with limited and 2 with diffuse SSc, with a severe and refractory joint involvement were enrolled in the study. Methotrexate and cyclophosphamide pulse therapy did not ameliorate joint symptoms. Hence, intravenous immunoglobulins therapy was prescribed at a dosage of 2 g/kg body weight during 4 days/month for six consecutive courses. The presence of joint tenderness and swelling, and articular deformities (due to primary joint involvement and not due to skin and subcutaneous changes) were evaluated. Before and after 6 months of treatment, patients were subjected to (1) Ritchie Index (RI) evaluation of joint involvement; (2) Dreiser Algo-Functional Index (IAFD) evaluation of hand joint function; (3) pain visual analogue scale (VAS) to measure joint pain; (4) Health Assessment Questionnaire (HAQ) to evaluate the limitations in everyday living and physical disability; and (5) modified Rodnan Skin Score for skin involvement. Results: After 6 months of intravenous immunoglobulins therapy, joint pain and tenderness, measured with the VAS, decreased significantly (p<0.03), and hand function (IAFD) improved significantly (p<0.02), together with the quality of life (HAQ; p<0.03). All patients significantly improved, except for one. The skin score after 6 months of intravenous immunoglobulins therapy was significantly reduced (p<0.003). Conclusion: This pilot study suggests that intravenous immunoglobulins may reduce joint pain and tenderness, with a significant recovery of joint function in patients with SSc with severe and refractory joint involvement. The cost of intravenous immunoglobulins might limit their use only to patients who failed disease-modifying antirheumatic drugs.